Biologic Response of Inguinal Hernia Prosthetics: A Comparative Study of Conventional Static Meshes Versus 3D Dynamic Implants. Issue 1 (January 2015) - Amato, Giuseppe; Romano, Giorgio; Agrusa, Antonino; Marasa, Salvatore; Cocorullo, Gianfranco; Gulotta, Gaspare; Goetze, Thorsten; Puleio, Roberto
Abstract Despite improvements in prosthetics and surgical techniques, the rate of complications following inguinal hernia repair remains high. Among these, discomfort and chronic pain have become a source of increasing concern among surgeons. Poor quality of tissue ingrowth, such as thin scar plates or shrinking scars—typical results with conventional static implants and plugs—may contribute to these adverse events. Recently, a new type of 3D dynamically responsive implant was introduced to the market. This device, designed to be placed fixation‐free, seems to induce ingrowth of viable and structured tissue instead of regressive fibrotic scarring. To elucidate the differences in biologic response between the conventional static meshes and this 3D dynamically responsive implant, a histological comparison was planned. The aim of this study was to determine the quality of tissue incorporation in both types of implants excised after short, medium, and long periods post‐implantation. The results showed large differences in the biologic responses between the two implant types. Histologically, the 3D dynamic implant showed development of tissue elements more similar to natural abdominal wall structures, such as the ingrowth of loose and well‐hydrated connective tissue, well‐formed vascular structures, elastic fibers, and mature nerves, with negligible or absent inflammatory response. All these characteristics were completely absent in the conventional static implants, where a persistent inflammatory reaction was associated with thin, hardened, and shrunken fibrotic scar formation. Consequently, as herniation is a degenerative process, the 3D dynamic implants, which induce regeneration of the typical groin components, seem to address its pathogenesis.